Características fitoquímicas del pericarpio y la semilla del fruto de Garcinia mangostana L. según el método de extracción (2016)
The main objective of this research was the evaluation of several methods of extraction of metabolites from the pericarp and seed of Garcinia mangostana L. fruit. These substances appear to be responsible, at least in part, for the beneficial role in health and for establishing the mechanisms by which they perform their action “in vivo”. After receiving and disinfecting the fruit samples, three solutions using the extraction methods of: Soxhlet, hydrodistillation and steam stripping, were obtained. The solutions were subjected to a preliminary phytochemical analysis which included the following tests: Shinoda, Rosenhein and leucoantocianidinas for flavonoids, ferric chloride and lead acetate for the qualification of tannins and foam reaction for saponins and cardiotonics. A two-factor design was used, being the first factor the extraction method, with three levels and, the second factor, used fruit part, with two levels. As a main result was obtained that both the pericarp and seed of G. mangostana L. contain a high phytochemical potential, evidenced by the presence of flavonoids and tannins. © 2016, Universidad Nacional de Colombial. All rights reserved.